A COMPARATIVE STUDY ON THE EFFECTS OF USING A ROLE PLAY AND A SMALL GROUP DISCUSSION TOWARDS THE SEVENTH GRADE STUDENTS’ SPEAKING ACHIEVEMENT AT SMP NEGERI 1 BANJAR - N.K. Ningrum; Sudirman Sudirman; N.K. Wedhanti (Language and Education Journal Undiksha, 2019)
This study aimed at investigating if there was difference in speaking achievement between students who were taught using role play and those taught using small group discussion. This study used quasi-experimental research design with post-test only control group design. Samples of this study were VII H and VII G. VII H as experimental group and VII G as control group. The samples were taken by random sampling technique. The instrument for collecting data was performance speaking test. The data were analyzed using descriptive analysis and inferential analysis. Result showed that mean score of experimental group was 78.53, while mean score of control group was 73.12. Hypothesis testing showed that the value of sig. (2-tailed) was 0.001. Since the value of sig (0.001) < 0.05, the value of tobserved exceeded the value of tcritical value. In conclusion, there was a difference in speaking achievement between the two methods.